"Do libraries still exist?" challenges and opportunities to an effective role of libraries in Egypt. - Shehata, Radwa Magdy (AUC Knowledge Fountain, 2016)
Public libraries are vital public agencies consist of the knowledge empowerment and the information accessibility. This study focuses on the role of public libraries toward serving society in Egypt. It addresses various provided services as well as the actual beneficiaries. The collected data is based on a qualitative study through semi structured interviews with librarians to focus on the existing functionality of public libraries. The main question is how the Egyptian public libraries can serve the society with the concentrate on the challenges they are facing and the possible opportunities for effective utilization. The interview data reflect the strong social mission that libraries have and their role in providing reference and reader services aside from organizing varied activities and supporting the lifelong learning. The study demonstrated the actual challenges which included the librarians’ limited training chances as well as their low wages. In addition to the uncooperative polices by the government and the lack of financial resources which required efficient running of the public libraries. On the other hand, the opportunities included the chances to enhance the librarians’ skills, raising fund, new policies that encouraged cooperation programs among libraries and other organizations, and the buildings spaces’ utilization as well as strengthening the infrastructure.